(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2019)
Origination of defects and loss of Na during the sintering process are the major problems for the conventional solid-state synthesis technique to form sodium (Na) doped lanthanum manganite. To minimize defect and Na loss during the sintering process, the sodium (Na) doped lanthanum manganite with 15% substitution of La by Na (La0.85Na0.15MnO3) was synthesized using the NaCl flux material incorporated with the conventional solid-state reaction technique (flux method). The amount of micro strain, lattice strain and dislocation density for the flux method to grow polycrystalline La0.85Na0.15MnO3were detected successfully. The structural study using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Scanning Electron Microscopy (SEM) and Energy Dispersive Analysis X-Ray (EDAX) showed that the use of flux synthesis technique instead of conventional solid-state reaction technique was satisfactory to obtain stoichiometric La0.85Na0.15MnO3 polycrystalline structure with a smaller defect. From the closer inspection of the XRD spectrum for La0.85Na0.15MnO3 significantly showed a higher order layered structure for the cathode material for using this flux technique, which is a very important feature to increase the efficiency of the cathode material. Bangladesh J. Sci. Ind. Res.54(4), 289-296, 2019